A Retrospective Descriptive Study on Caesarean Isthmocele: A Delayed and Under-recognised Complication of Caesarean Section - Maneesha Shrivastava; Varuna Pathak; Sushruta Shrivastava (Journal of Clinical and Diagnostic Research)
Introduction: A caesarean scar defect (isthmocele) is an indentation that represents myometrial discontinuity in the anterior uterine wall, with the base communicating with the uterine cavity at the site of a previous caesarean section scar. It has been linked to a variety of gynaecological symptoms, including abnormal uterine bleeding and secondary infertility. Aim: To describe the demographic characteristics, clinical presentation, management and outcomes in patients with Caesarean Scar Defect (CSD). Materials and Methods: A retrospective cohort analysis was conducted in the Department of Obstetrics and Gynaecology, Gastrocare Hospital (tertiary care centre), Bhopal, Madhya Pradesh, India, from February 2020 to February 2023. Data were collected from the hospital records of 43 patients who presented with CSD. The recorded variables included demographic details, clinical presentations, prior treatments, diagnostic interventions, types of surgical procedures performed and patient outcomes. Descriptive statistics, such as means, standard deviations and frequencies, were used to summarise patient characteristics and outcomes. All statistical analyses were performed using Statistical Package for the Social Sciences (SPSS) software version 29.0 software. Results: The majority of the women were in the age group of 30-40 years. Out of 43 patients, eight presented with Abnormal Uterine Bleeding (AUB), three had secondary infertility, and 32 presented with Caesarean Scar Ectopic Pregnancy (CSEP) and its complications. All cases were managed either by hysteroscopy or laparoscopy, based on the Residual Myometrium Thickness (RMT). Conclusion: Transvaginal Sonography (TVS) is an effective tool for diagnosing CSD and CSEP. Surgical management can be guided by the RMT as determined by TVS.